Electrochemical performance and efficiency of novel copper hexacyanoferrate/graphitic carbon nitride composites for the removal of 137Cs - Sudarat Issarapanacheewin; Natthaya Siangdee; Poomsith Thangsan; Witsanu Katekaew; Nikom Prasertchiewchan; Wilasinee Kingkam; Kanlayawat Wangkawong (Electrochemistry Communications)
This study investigates the use of a novel composite material, synthesized from melamine, urea, and thiourea derived graphitic carbon nitride (g-C3N4) and copper hexacyanoferrate (CuHCF) by ultrasonication method, for the electrochemical adsorption of 137Cs in wastewater. The adsorption and desorption of Cs+ ions in the CuHCF/g-C3N4 composite can be investigated using cyclic voltammetry by alternating the applied potentials between the anode and cathode. Different g-C3N4 precursors alter the structural and electrochemical properties of the composites, affecting surface area, porosity, electron transfer, and performance in 137Cs adsorption. The novel composite materials demonstrated a significant removal efficiency that calculated to be 46.5 % for pure CuHCF, 50.6 % for CuHCF/g-C3N4-M, 59.8 % for CuHCF/g-C3N4-U, and 52.5 % for CuHCF/g-C3N4-T, utilizing an electrochemical method over 250 cycles. The proposed system was successfully employed to adsorb 137Cs from actual wastewater. This method underscores the potential of the CuHCF/g-C3N4 composite as a promising candidate for the sustainable and effective removal of radioactive 137Cs from contaminated water sources.